Patient experiences of fertility clinic closure during the COVID-19 pandemic: appraisals, coping and emotions. Issue 11 (24th October 2020) - Boivin, J; Harrison, C; Mathur, R; Burns, G; Pericleous-Smith, A; Gameiro, S
Abstract: STUDY QUESTION: What are appraisals, coping strategies and emotional reactions of patients to coronavirus disease 2019 (COVID-19) fertility clinic closures? SUMMARY ANSWER: Clinic closure was appraised as stressful due to uncertainty and threat to the attainability of the parenthood goal but patients were able to cope using strategies that fit the uncertainty of the situation. WHAT IS KNOWN ALREADY: Psychological research on COVID-19 suggests that people are more anxious than historical norms and moderately to extremely upset about fertility treatment cancellation owing to COVID-19. STUDY DESIGN, SIZE, DURATION: The study was of cross-sectional design, comprising a mixed-methods, English language, anonymous, online survey posted from April 9 to 21 to social media. Eligibility criteria were being affected by COVID-19 fertility clinic closure, 18 years of age or older and able to complete the survey in English. In total, 946 people clicked on the survey link, 76 did not consent, 420 started but did not complete the survey and 450 completed (48% completion, 446 women, four men). PARTICIPANTS/MATERIALS, SETTING, METHODS: Overall 74.7% (n = 336) of respondents were residents in the UK with an average age of 33.6 years (SD = 4.4) and average years trying to conceive, 3.5 years (SD = 2.22). The survey comprised quantitative questions about the intensity of cognitive appraisals and emotions about clinic closure, and ability to cope with clinic closure. Open-text questions covered their understanding of COVID-19 and its effect on reproductive health and fertility plans, concerns and perceived benefits of clinic closure, and knowledge about closure. Sociodemographic information was collected. Descriptive and inferential statistics were used on quantitative data. Thematic qualitative analysis (inductive coding) was performed on the textual data from each question. Deductive coding grouped themes from each question into meta-themes related to cognitive stress and coping theory. MAIN RESULTS AND THE ROLE OF CHANCE: Most patients (81.6%, n = 367) had tests or treatments postponed, with these being self (41.3%, n = 186) or publicly (46.4%, n = 209) funded. Patients appraised fertility clinic closure as having potential for a more negative than positive impact on their lives, and to be very or extremely uncontrollable and stressful ( P ≤ 0.001). Most reported a slight to moderate ability to cope with closure. Data saturation was achieved with all open-text questions, with 33 broad themes identified and four meta-themes linked to components of the cognitive stress and coping theory. First, participants understood clinic closure was precautionary due to unknown effects of COVID-19 but some felt clinic closure was unfair relative to advice about getting pregnant given to the public. Second, closure was appraised as a threat to attainability of the parenthood goal largely due to uncertainty of the situation (e.g. re-opening, effect of delay) and intensification of pre-existing hardships of fertility problems (e.g. long time waiting for treatment, history of failed treatment). Third, closure taxed personal coping resources but most were able to cope using thought-management (e.g. distraction, focusing on positives), getting mentally and physically fit for next treatments, strengthening their social network, and keeping up-to-date. Finally, participants reported more negative than positive emotions ( P ≤ 0.001) and, almost all participants reported stress, worry and frustration at the situation, while some expressed anger and resentment at the unfairness of the situation. Overall, 11.8% were not at all able to cope, with reports of intense feelings of hopelessness and deteriorating well-being and mental health. LIMITATIONS, REASONS FOR CAUTION: The survey captures patient reactions at a specific point in time, during lockdown and before clinics announced re-opening. Participants were self-selected (e.g. UK residents, women, 48% starting but not completing the survey), which may affect generalisability. WIDER IMPLICATIONS OF THE FINDINGS: Fertility stakeholders (e.g. clinics, patient support groups, regulators, professional societies) need to work together to address the great uncertainty from COVID-19. This goal can be met proactively by setting up transparent processes for COVID-19 eventualities and signposting to information and coping resources. Future psychological research priorities should be on identifying patients at risk of distress with standardised measures and developing digital technologies appropriate for the realities of fertility care under COVID-19. STUDY FUNDING/COMPETING INTEREST(S): University funded research. Outside of the submitted work, Prof. J.B. reports personal fees from Merck KGaA, Merck AB, Theramex, Ferring Pharmaceuticals A/S; grants from Merck Serono Ltd; and that she is co-developer of the Fertility Quality of Life (FertiQoL) and MediEmo apps. Outside of the submitted work, Dr R.M. reports personal or consultancy fees from Manchester Fertility, Gedeon Richter, Ferring and Merck. Outside of the submitted work, Dr S.G. reports consultancy fees from Ferring Pharmaceuticals A/S, Access Fertility and SONA-Pharm LLC, and grants from Merck Serono Ltd. The other authors declare no conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.